Hospital Emergency Unit Services Reviewed from Legal Aspects: A Case Study of Marthen Indey Hospital, Jayapura - Adya Seta, Astrodita (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2024)
Emergency Room (ER) services in hospitals play a vital role in providing first aid to patients in medical emergencies. This study aims to review the legal aspects of ER services, especially regarding the contract between doctors and patients, the obligation to provide assistance, and the role of on-call doctors. The methods used in this study include literature review and legal analysis of applicable laws and regulations, such as Law No. 17 of 2023 concerning Health. The results of the study indicate that the legal aspects of the contract regulate the rights, obligations, and responsibilities of doctors and patients. Doctors are obliged to provide first aid without delay and maintain the confidentiality of patient medical information. Article 189 point c of Law No. 17 of 2023 concerning Health emphasizes the obligation of hospitals to provide emergency services to patients according to their service capabilities. A good understanding of these legal aspects is important to ensure that ER services run in accordance with ethical and legal standards, as well as to avoid potential legal disputes.